Design of a high-power harmonic waveguide filter for radar transmitter - Trịnh, Xuân Thọ; Pham Huu Lap; Tran Van Ha (Journal of Military Science and Technology, 2024)
In this article, we present the research results on the designing and manufacturing method of a high-power harmonic filter applied in the X-band transmitter system. The harmonic filter utilizes Waffle-iron filters and quarter-wavelength converters on the waveguide. As a result, the loss and ripple within the passband are improved, while meeting the requirements of cutting off high-order harmonics. Based on the application of microwave theory and simulation software tools, the research team have calculated, designed and manufactured a harmonic filter that meets all the requested specifications for application in X-band transmitter systems: Loss ≤ 0,12dB@8,9-9,6GHz; Reflection coefficient ≤ -20dB@8,9-9,6GHz; Frequency selectivity ≤ -40dB@2nd harmonic, 3rd harmonic, 4th harmonic.